SYSTEM MOTORCYCLE SPARE PARTS SALE INFORMATION AT KIEL JAYA MANDIRI WORKSHOP - Rafiqa Rizalita; Maria. MC Tampubolon (INFOKUM, 2019)
The motorcycle spare part sales information system at the Kiel Jaya Mandiri Workshop, Pematangsiantar City is a system that provides information services in the form of purchase transaction data and sales reports of goods data and stock of goods. So far, the recording of sales transactions of goods, goods data, and stock of goods is still done manually so that the sales calculation transaction process often results in errors. With the existence of a motorcycle spare part sales information system at the Kiel Jaya Mandiri workshop, it can help the process of recording sales transactions so that data processing is faster and more efficient.